Eksistensi Hukuman Pidana Mati Dalam Undang-Undang Nomor 1 Tahun 2023 Tentang KUHP - Deri Ardiansyah; Muhammad Adiaat; Aditya Indah Cahyani; Nurlaili Rahmawati (Rampai Jurnal Hukum (RJH), 2024)
This research aims to discuss the existence of the death penalty in Law Number 1 of 2023 concerning the Criminal Code and look at the advantages and disadvantages of the death penalty in Article 100 of the National Criminal Code. This research is normative juridical research using a statutory approach, case approach and concept approach. The results of this research are that Article 100 paragraph (1) of the National Criminal Code listed that, executing criminal dead determined by delaying criminal death for 10 (10) years taking into account two conditions namely, a feeling of regret and wanting to repent for it repair self as well as role defendant criminal dead in follow criminal. The death penalty in the National Criminal Code has advantages and disadvantages, the advantages are punishment dead arranged as a criminal alternative and existence delays the execution of criminal dead, so it can become a road middle between the pros and cons views of criminal punishment. In fact, the punishment dead is the most severe punishment, because of its implementation The death penalty is only given to perpetrators of serious crimes such as premeditated murder, so the death penalty is responsible for their actions and will have a deterrent effect. Meanwhile, the weakness of the regulation of the death penalty in Article 110 paragraph (1) of the National Criminal Code is that there is no legal certainty regarding when the death penalty is carried out, which has an impact on the execution of people waiting for the trial period. This makes criminal cases too long, the judicial process is uncertain what verdict will be received, and the deadline for issuing a presidential decision by obtaining the consideration of the Supreme Court is not clearly regulated. Abstrak Penelitian ini bertujuan untuk membahas tentang eksistensi hukuman mati dalam Undang-Undang Nomor 1 Tahun 2023 tentang KUHP serta melihat kekurangan dan kelebihan dari pidana mati dalam Pasal 100 KUHP nasional. Penelitian ini merupakan penelitian yuridis normatif dengan menggunakan pendekatan undang-undang, pendekatan kasus dan pendekatan konsep. Hasil penelitian ini adalah Pada Pasal 100 ayat (1) KUHP Nasional tercantum bahwa, eksekusi pidana mati ditentukan oleh penundaan pidana mati selama 10 (sepuluh) tahun yang memperhatikan dua syarat yaitu, rasa penyesalan dan mau bertaubat untuk memperbaiki diri serta peran terdakwa pidana mati dalam tindak pidana. Pidana Mati dalam KUHP Nasional mempunyai kelebihan dan kekurangan, kelebihannya adalah hukuman mati diatur sebagai pidana alternatif dan adanya penundaan eksekusi pidana mati, sehingga dapat menjadi jalan tengah antara pandangan pro dan kontra terhadap pidana hukuman mati. Faktanya, hukuman mati merupakan hukuman yang paling berat, karena penerapannya vonis hukuman mati hanya diberikan kepada pelaku tindak pidana kelas berat seperti pembunuhan berencana, sehingga hukuman mati merupakan pertanggungjawaban atas perbuatannya dan akan menimbulkan efek jera. Sedangkan kelemahan pengaturan hukuman mati dalam Pasal 110 ayat (1) KUHP Nasional ini adalah tidak ada kepastian hukum mengenai kapan dilaksanakannya hukuman mati berdampak pada pelaksanaan eksekusi mati yang menunggu masa percobaan. Hal ini membuat perkara pidana terlalu lama, proses peradilan tidak ada kepastian putusan apa yang akan diterimanya, dan batas waktu dikeluarkannya putusan Presiden dengan mendapatkan pertimbangan Mahkamah Agung tidak diatur secara jelas.